Effect of contamination towards Proton exchange membrane fuel cell performance: a review on experimental and numerical works - Muhammad Lebai Rodin; Saiful Hasmady Abu Hassan; Zulfirdaus Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2020)
Proton exchange membrane fuel cell (PEMFC) is a well-known energy converter that has low greenhouse gases (GHG) emission, low operating temperatures, and high power density. PEMFC operates on hydrogen (H2 ) as fuel, and oxygen (O2 ) as oxidant. Inverse electrolysis occurs between the oxidant and the fuel. Then, water (H2O) forms as their by product. Practically, O2 is supplied from the free air which contains not only oxygen but also other gases such as sulphur dioxide (SO2 ), and nitrogen oxides (NOx). Meanwhile, the H2 fuel may contain traces of carbon monoxide (CO) as a result from its previous reforming process. This makes PEMFC susceptible to disruption from these particles. These contaminating gases from the free air occupy the reacting sites originally meant for O2 and react with hydrogen ions instead of oxygen ions. While minute CO traces from the fuel occupies the reacting sites for H2 and react with oxygen ions instead of hydrogen ions. Consecutively, the energy output from the PEMFC will be short from its expected numerical value hence a less efficient PEMFC. Hence, this paper reviews recent research on PEMFC under the impact of cathode and anode side contaminants via experimental and numerical works. It is found that CO has more effect to the cell compared to CO2 . SO2 and CO contaminates the catalyst layer while NOx does not. In addition, PtRu/C shows more resistance to contamination compared to traditional Pt/C. This comparative review serves to find out potentials in improving PEMFC operation and solving its mitigation strategies.